ІNSTITUTIONALIZATION OF THE GLOBAL MARKET FOR SPORTS GOODS - NEUKHATSKA, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides an expanded and in-depth examination of the institutionalization process within the global sporting goods market, emphasizing its decisive role in shaping the market’s structure, operational dynamics, and long-term development trajectories in the global economy. In the context of steadily increasing consumer demand, rapid technological innovation, digitalization of marketing channels, and the growing influence of global brands, the study investigates how stable norms, regulatory frameworks, and mechanisms of interaction emerge and evolve among the principal stakeholders—manufacturers, consumers, distributors, retail chains, international organizations, and national regulatory bodies. Special emphasis is placed on the strategic influence of major transnational corporations such as Nike, Adidas, and Puma, which continuously redefine industry standards by setting trends in product design, sustainability initiatives, production technologies, ethical sourcing practices, and global supply-chain management. The article details the sequential stages of institutionalization, including the creation of a coherent international regulatory base, the harmonization and standardization of product quality requirements, the spread of certification systems, the development of mechanisms ensuring fair competition, and the increasing integration of environmental and social responsibility criteria. The research also highlights the challenges confronting the market, such as intensified global competition, shifts in consumer behavior toward more conscious and ethical consumption, the growing importance of sustainability, and the need to adapt to geopolitical instability and changing trade policies. In addition, the study explores how digital transformation, e-commerce platforms, and data-driven marketing reshape traditional market institutions and contribute to more transparent and traceable supply chains. The author argues that institutionalization strengthens trust, accountability, and efficiency across all levels of market interaction while simultaneously expanding opportunities for national producers seeking integration into global trade networks. Ultimately, institutionalization is conceptualized as a complex, multidimensional process that encompasses legal, economic, environmental, and socio-cultural dimensions, creating the essential conditions for the long-term resilience, innovative capacity, and competitive adaptability of the global sporting goods market.